PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR IPS MELALUI PAKEM DENGAN BANTUAN MEDIA PADA SISWA KELAS VIIIA SMP NEGERI 1 KANDEMAN BATANG TAHUN PELAJARAN 2013/2014 (Faculty of Social Science, Universitas Negeri Semarang, 2014)
The purpose of this research is to improve: (1) The active participation of student learning, (2) the attitude of students towards learning social studies, (3) Complete results of social studies. Subjects of this study 40 eighth grade students of SMP N 1 Kandeman A Trunk academic year 2013 / 2014.Teknik data collection used were: observation, interview, questionnaire, achievement test, documentation, and field notes. Data analysis using quantitative analysis. The results of the study are as follows. (1) There is an average increase of eight observations activeness of student learning, in the first cycle mean score of 64.69 (high); second cycle mean score of 71.94 (high), the third cycle mean score of 84.50 (very high). (2) There is an increase in students' attitudes toward learning social studies, the mean value of the first cycle 68 (good), the average value of the second cycle 77 (good), and the mean value of the third cycle 85.75 (very good). (3) There is an increasing mastery IPS student learning outcomes, in the first cycle learning AJEL strategy, media, liveliness, and learning outcomes completeness 67.5% with a mean value of 74, the second cycle, 77.5% with a mean value of 78, the third cycle of 85% with a mean value of 83.65. By usin three different media in each cycle there are three prominent increase in activity in the ranking are: pay attention to the material, noting the results of the discussion, and the spirit in the move. Thus the use AJEL strategy with the help of the media in social studies learning can enhance